Developing a dashboard for program evaluation in competency-based training programs: a design-based research project - Yusuf Yilmaz; Robert Carey; Teresa Chan; Venkat Bandi; Shisong Wang; Robert A Woods; Debajyoti Mondal; Brent Thoma (Canadian Medical Education Journal, 2022)
Background: Canadian specialist residency training programs are implementing a form of competency-based medical education (CBME) that requires the assessment of entrustable professional activities (EPAs). Dashboards could be used to track the completion of EPAs to support program evaluation.